Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on Neuroablative Procedures for Patients With Cancer Pain. Issue 3 (23rd December 2020) - Raslan, Ahmed M; Ben-Haim, Sharona; Falowski, Steven M; Machado, André G; Miller, Jonathan; Pilitsis, Julie G; Rosenberg, William S; Rosenow, Joshua M; Sweet, Jennifer; Viswanathan, Ashwin; Winfree, Christopher J; Schwalb, Jason M
Abstract: BACKGROUND: Managing cancer pain once it is refractory to conventional treatment continues to challenge caregivers committed to serving those who are suffering from a malignancy. Although neuromodulation has a role in the treatment of cancer pain for some patients, these therapies may not be suitable for all patients. Therefore, neuroablative procedures, which were once a mainstay in treating intractable cancer pain, are again on the rise. This guideline serves as a systematic review of the literature of the outcomes following neuroablative procedures. OBJECTIVE: To establish clinical practice guidelines for the use of neuroablative procedures to treat patients with cancer pain. METHODS: A systematic review of neuroablative procedures used to treat patients with cancer pain from 1980 to April 2019 was performed using the United States National Library of Medicine PubMed database, EMBASE, and Cochrane CENTRAL. After inclusion criteria were established, full text articles that met the inclusion criteria were reviewed by 2 members of the task force and the quality of the evidence was graded. RESULTS: In total, 14 646 relevant abstracts were identified by the literature search, from which 189 met initial screening criteria. After full text review, 58 of the 189 articles were included and subdivided into 4 different clinical scenarios. These include unilateral somatic nociceptive/neuropathic body cancer pain, craniofacial cancer pain, midline subdiaphragmatic visceral cancer pain, and disseminated cancer pain. Class II and III evidence was available for these 4 clinical scenarios. Level III recommendations were developed for the use of neuroablative procedures to treat patients with cancer pain. CONCLUSION: Neuroablative procedures may be an option for treating patients with refractory cancer pain. Serious adverse events were reported in some studies, but were relatively uncommon. Improved imaging, refinements in technique and the availability of new lesioning modalities may minimize the risks of neuroablation even further. The full guidelines can be accessed at https://www.cns.org/guidelines/browse-guidelines-detail/guidelines-on-neuroablative-procedures-patients-wi .